Effect of interference fit size on local stress in single lap bolted joints. (15th June 2015) - Bi, Yunbo; Jiang, Jiefeng; Ke, Yinglin
The interference fit is an effective process technique to improve the fatigue life of aircraft structures. In this article, the experiments including the interference fit bolt installation and tensile loading in bolted joint were carried out. A three-dimensional finite element model was established to simulate the experimental process, and the finite element model was validated by comparing the simulated data with the experimental data of the squeeze forces and the strains. By finite element simulation and analysis, it can be concluded that the location of maximum value of the maximum principal stress on the upper plate faying surface is going far away from the hole edge with the increase in interference fit size. Furthermore, by analyzing the hoop stress variations along a prescribed path, the maximum value of the hoop tensile stress is smallest at the interference fit size of 1.5%.